CD38+ Liver Stellate Cells in Chronic Hepatitis C Patients with Fibrosis - Titos Ahimsa; Rino Alvani Gani; Ari Fahrial Syam; Suhendro - - (The Indonesian Society for Digestive Endoscopy, 2015)
Background: Approximately 3% of the world population is infected with hepatitis C virus (HCV). Protein of hepatitis C virus modulates apoptosis and steatosis, liver cell injury, activates liver stellate cells and liver fibrosis. Hepatitis C virus infection will cause injury to the hepatocytes. This injury to the hepatocyte will activate liver stellate cells. Stellate cells have a huge role in the development of liver fibrosis. The objective of this study is to evaluate the difference of active CD38+ liver stellate cells in various degree of fibrosis as well as its relation with aspartate transaminase (AST), alanine transaminase (ALT), and quantitative amount of hepatitis c virus ribonucleic acid (HCV RNA) in chronic hepatitis C.Method: This study was a cross-sectional study performed in 32 patients with chronic hepatitis C who had undergone liver USG, did not suffer from hepatoma, had undergone liver biopsy. Paraffin block of patients’ liver tissue was further stained using Haematoxylin and Eosin technique to identify the Metavir degree which is categorized into mild-moderate or severe degree. Special staining is performed to evaluate liver stellate cells that were then counted in averagely in five fields of view.Results: In this study, we found significant difference in the amount of CD38+ stellate liver cells between severe and mild-moderate fibrosis (p 0.001), there was no association between CD38+ stellate liver cells with AST (p = 0.2) or ALT (p = 0.7), and there was association between CD38+ stellate liver cells with quantitative HCV RNA (r = -0.372).Conclusion: Total amount of CD38+ stellate liver cells in severe fibrosis was higher compared to the total amount of CD38+ liver stellate cells in mild-moderate fibrosis. There was no association between the value of AST, ALT, and quantitative HCV RNA with the number of CD38+ stellate liver cells.